تأثير التغذية بالمكعبات العلفية (مخلفات تقليم الزيتون ) في بعض المؤشرات الإنتاجية عند الحملان - جمول, عادل (Latakia University Journal -Biological Sciences Series, 2016)
نفذ هذا البحث في مركز فديو لتربية الأبقار والأغنام التابع لقسم الإنتاج الحيواني في كلية الزراعة في جامعة تشرين مع بداية فصل الربيع من عام 2011 بهدف دراسة إمكانية إحلال المكعبات العلفية محل جزء من العلف المركز في علائق تسمين الحملان وتأثير ذلك على أدائها , باستخدام / 20 / عشرون ذكراً من سلالة العواس تراوحت أعمارها بين 4- 5 أشهر ومتوسط أوزانها 23.5 كغ ووزعت على أربعة مجموعات لتقييم المعاملات التجريبية من خلال تجارب نمو وتجارب هضم ( طبقاً لمقرارات 1996 NRC ) أهم النتائج :- بزيادة مخلفات بقايا تقليم الزيتون في العلائق المختبرة تزيد المادة الجافة المأكولة يومياً عن العليقة الشاهد ولكن بدون فروق معنوية .- كانت الزيادة اليومية في الوزن 150- 151 – 144- 134 g C-G1-G2-G3 على التوالي / باليوم والكفاءة التحويلية للغذاء C-G1-G2 9.66-9.80-10.27 على التوالي كانت متقاربة بينما كانت الكفاءة التحويلية للمعاملة G3-11.11 أقل بالمقارنة مع المعاملات الثلاثة السابقة الذكر أعلاه التي انخفضت بعض الشىء- معامل هضم المادة الجافة والمادة العضوية بالنسبة للمعاملة G1 كانت أعلى وبفارق معنوي على مستوى ( 0.05 > P ) بالمقارنة مع المعاملة G3 جدول ( 7) , بينما معامل هضم البروتين الخام للمعاملة G3 كان أقل بالمقارنة مع بقية المعاملات على مستوى معنوية (0.05 > P ) .- معامل هضم الالياف الخام والدهن الخام للمعاملات G3-G2 كانت اعلى بالمقارنة مع الكونترول C على مستوى معنوية (0.05 > P ) .This this research was Carried out at video cattle and sheep Center of the Department of Animal Production in the College of Agriculture in October University with the beginning of the spring of 2011 in order to study the possibility of bringing cubes forage replace part of the feed position in the diets of fattening lambs and the impact on their performance, using / 20 / Twenty male strain of Awas ages ranged between 4-5 months and the average weight of 23.5 kg and distributed to four groups to evaluate (in accordance with the decisions of 1996 NRC) the experimental treatments- An increase of waste residue olive trim diets tested in dry matter ingested more than a day for the bush CONTROL but without significant differences.- The daily increase in weight 150- 151 - 144- 134 g C-G1-G2-G3 respectively / day and feed conversion C-G1-G2 9.66-9.80-10.27 respectively were close while the manufacturing efficiency of the transaction G3-11.11 lower compared with the previous three transactions mentioned above, which fell somewhat - Digestible dry matter plants and organic matter for the treatment of G1 was the highest with significant at the level of (0.05> P) compared with treatment G3 table (5), while the digestion of crude protein for the treatment of G3 coefficient was lower compared with the rest of the transactions on the abstract level (0.05> P ).- Digest raw fiber and raw fat transactions G3-G2 coefficient was higher compared with the Control C on the abstract level (0.05> P),